Browning Prevention Method in Kepel (Stelechocarpus burahol (Blume) Hook.f. & Thomson) in Vitro Culture - Devi Sonti Sibarani; Ratih Restiani; Aniek Prasetyaningsih (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS (JPBN), 2024)
Browning of explants is a common problem in Kepel (Stelechocarpus burahol (Blume) Hook.f. & Thomson) in vitro culture, resulting in low explant in vitro regeneration of Kepel. Using nodal explant, the effect of explant immersion in ascorbic acid, the addition of ascorbic acid to the media, and dark and light incubation conditions were investigated. The browning prevention method was selected based on the delayed browning appearance time, the lowest broning intensity, and the highest percentage of callus. This present study used a completely randomized design with treatment variations: immersion explant in ascorbic acid 100 mg/L, addition of ascorbic acid 100 and 200 mg/L to the media, addition of ascorbic acid 100 and 200 mg/L and activated charcoal 1 g/L to the media, and incubation in dark and light conditions for 28 days. The results showed that the combination of the addition of ascorbic acid 200 mg/L to MS media and incubation in dark conditions were effective browning prevention methods in inhibiting browning appearance time (5 DAP), significantly reducing browning intensity (0.3), and increasing callus growth (100%) of kepel node explants during 28 days of culture. The results of this study are useful in establishing protocols for in vitro culture of Kepel plants, especially at the initiation stage, and can be expected to support the successful conservation of Kepel plants through in vitro propagation. Keywords: Ascorbic acid, Activated Charcoal, Browning, In Vitro Culture, Stelechocarpus burahol